F. Gracia, A Alonso, O. Munilla Cabrillana y R. Pallarés Comas. La Moleta del Remel, Alcanar-Montsia. Campañas 1985-1986. Tarragona, Publicación de la Diputación de Tarragona, 1988. (ISBN: 84-87123-01-5) - López Pardo, Fernando (Gerión. Revista de Historia Antigua, 1991)
Sin resumen